2014
DOI: 10.1089/pho.2014.3741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Laser Therapy on Radiotherapy-Induced Hyposalivation and Xerostomia: A Pilot Study

Abstract: With the parameters used, LLLT was not able to increase SFR or decrease xerostomia. The results may be associated with the late effects of radiotherapy on glandular structure, such as fibrosis and acinar atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 43 publications
2
56
0
7
Order By: Relevance
“…Two studies assessed salivary flow one or more weeks after completion of the experimental treatment [31,33] whereas the timing of salivary flow collection at endpoint remained unclear in three studies [21,23,25]. or more weeks after completion of the intervention [31,33], whereas timing of outcome collection was unclear in three studies [26,29,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies assessed salivary flow one or more weeks after completion of the experimental treatment [31,33] whereas the timing of salivary flow collection at endpoint remained unclear in three studies [21,23,25]. or more weeks after completion of the intervention [31,33], whereas timing of outcome collection was unclear in three studies [26,29,34].…”
Section: Resultsmentioning
confidence: 99%
“…One trial tested the effectiveness of low-level laser therapy in improving xerostomia symptoms (VAS), salivary flow and quality of life (assessed through the Oral Health Impact Profile questionnaire) [23]. The groups underwent two weekly sessions of low-level laser therapy for six weeks but in the control group a plastic tip blocked the emission of radiation.…”
Section: Low-level Laser Therapy Vs Sham Low-level Laser Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased salivary flow was observed in HNC patients treated with RT [70]. A recent study performed in HNC patients at least 6 months following conventional RT found no improvement of hyposalivation and xerostomia, likely due to irreversible acinar atrophy and fibrosis [71]. …”
Section: Pbm For the Management Of Orofacial And Neck Complications Omentioning
confidence: 99%
“…6,7 Among the treatment modalities used to improve the sequelae of radiotherapy to the salivary glands, low-level laser therapy (LLLT) has produced favourable results in terms of tissue repair and biomodulation of the inflammatory process, [8][9][10][11][12][13] especially in clinical and histological studies evaluating the effects of LLLT on the salivary glands in the ionising radiation field. [14][15][16][17] Damage caused by radiotherapy to the stroma and structures involved in the process of salivary secretion has a direct impact on salivary production and flow. Water transport by the acinar cells for primary production of saliva occurs through specific proteins, namely aquaporins (AQPs).…”
Section: Introductionmentioning
confidence: 99%